Analisis Problematika Pembelajaran Bahasa Arab Pada Mahasiswa Program Study Pendidikan Bahasa Arab Universitas Al-Falah As-Sunniyah Kencong-Jember - Muhammad Insar Arief; Ahmad Mizan Rosyadi Abdul Jalil Mannan (EduInovasi: Journal of Basic Educational Studies, 2025)
Arabic is one of the subjects taught at Islamic higher education institutions in Indonesia, including at Al-Falah As-Sunniyah University. However, the teaching of Arabic at Al-Falah As-Sunniyah University often encounters various challenges, particularly those related to linguistic and non-linguistic issues. Moreover, problems in Arabic language instruction are closely linked to the developments of the times and advancements in technology. This article discusses the problems of Arabic language learning among students of the Arabic Language Education Study Program at Al-Falah As-Sunniyah University, Kencong-Jember, with the university serving as the case study location. This study uses a descriptive qualitative approach, with data collection techniques including interviews and observations. The findings indicate several problems that contribute to students’ difficulties in mastering Arabic, namely linguistic and non-linguistic issues. To overcome these obstacles, a contextual and practice-based learning approach is required, along with explicit integration of phonetic instruction, utilization of interactive technology, and adaptive, inclusive pedagogical strategies that consider students' cultural backgrounds and learning needs.